Coagulation Studies in a Case of Hageman Trait - Loeliger, E. A; Hensen, A (Thrombosis and Haemostasis, 1961)
After a brief review of the data concerning the cases of Hageman trait hitherto reported in the literature, a patient with severe Hageman factor (HF) “deficiency” (HF-activity below 0.05% of normal) is described. The patient has no haemorrhagic diathesis.In vitro, intrinsic coagulability and fibrinolytic activity are grossly disturbed. On the basis of a diminished fibrinolytic activity in vivo, the rather high activity of several coagulation factors in patient’s plasma could be explained.Thromboplastin formation, once initiated, is normal as to rate; the amount of thromboplastin formed is possibly slightly diminished. Prothrombin consumption is normal. These findings are in agreement with a normal rate ot clot formation, as measured by means of thrombelastography.Normal HF seems to be an initiator of blood coagulation only and not an activator or a substrate involved in thromboplastin formation.The weak anticoagulant property of Hageman trait plasma, described by several authors, is not necessarily due to an inhibitor; it can be explained by the assumption that, in Hageman trait, HF shows normal glass adsorbability and only a very deficient glass activation.